Russia in Flames : War, Revolution, Civil War, 1914-1921. - Engelstein, Laura (Oxford University Press, 2017)
To mark the centennial of the Bolshevik takeover of Russia, one of its greatest scholars has written a searing and defining account of the Russian Revolution, the fall of the old order, and the creation of the Soviet state.